2015
DOI: 10.1039/c5cp04412j
|View full text |Cite
|
Sign up to set email alerts
|

S⋯O chalcogen bonding in sulfa drugs: insights from multipole charge density and X-ray wavefunction of acetazolamide

Abstract: Experimental charge density analysis combined with the quantum crystallographic technique of X-ray wavefunction refinement (XWR) provides quantitative insights into the intra- and intermolecular interactions formed by acetazolamide, a diuretic drug. Firstly, the analysis of charge density topology at the intermolecular level shows the presence of exceptionally strong interaction motifs such as a DDAA-AADD (D-donor, A-acceptor) type quadruple hydrogen bond motif and a sulfonamide dimer synthon. The nature and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 61 publications
(55 reference statements)
4
61
0
Order By: Relevance
“…Our recent quantum crystallographic study on the drug acetazolamide and charge density analysis of sulfamethizole revealed a pair of ‘σ‐holes’ (electropositive regions formed in the direction of σ‐bonds) on the sulfur atom leading to conformation‐locking intra molecular S⋅⋅⋅O chalcogen bonding. Similarly, the salient directionality of sulfur–chalcogen bonding in riluzole must be linked to the positioning of ‘σ‐holes’ along the directions of S−C covalent bonds in this molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent quantum crystallographic study on the drug acetazolamide and charge density analysis of sulfamethizole revealed a pair of ‘σ‐holes’ (electropositive regions formed in the direction of σ‐bonds) on the sulfur atom leading to conformation‐locking intra molecular S⋅⋅⋅O chalcogen bonding. Similarly, the salient directionality of sulfur–chalcogen bonding in riluzole must be linked to the positioning of ‘σ‐holes’ along the directions of S−C covalent bonds in this molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Representative interaction motifs were selected manually from the complexes matching the d1 criterion for the complexes with Se‐containing ligands and from those matching the stricter d2 criterion and crystallographic resolution below 2 Å for the complexes with S‐containing ligands due to their large number. The C−S/Se⋅⋅⋅O/N/S angle was limited to 150–180°, which had been considered an optimal chalcogen‐bond angle range ,. It was also ensured that the electron densities were well defined.…”
Section: Resultsmentioning
confidence: 99%
“…Model systems (Table S1 and Figure S1) were selected manually from protein−ligand complexes found by the PDB survey with the criterion being the C−S/Se⋅⋅⋅O/N/S angle of 150–180°, which had previously been considered an optimal chalcogen‐bond angle range ,. The model systems with Se‐containing ligands were chosen from all the found complexes with a Se‐containing ligand (since they were not so numerous for manual scrutiny, Table 1) that matched the d1 distance criterion.…”
Section: Methodsmentioning
confidence: 99%
“…The study of intramolecular interactions is very important in the design of pharmaceutical drugs, particularly in the context of conformationally flexible molecules. Conformation-controlling intramolecular interactions in drug molecules have a direct influence on the binding modes of the drugs with the respective targets [53,54,55]. In particular, intramolecular peri-interactions have been widely studied in the literature in naphthalene and other related systems [56][57][58][59][60].…”
Section: The Importance In Drug Design Of Similar To Hb Bondsmentioning
confidence: 99%